Management of Mustard Aphid Lipaphis erysimi (Kalt.) (Homoptera: Aphididae) - Kafle, K. (International Journal of Applied Sciences and Biotechnology, 2015)
An experiment was conducted at IAAS, Lamjung to evaluate the management practices of Lipaphis erysimi (Kalt.) during Rabi season in 2013/14. Field experiment was laid out in a randomized block desigh (RCBD) with four replications and six treatments. The treatments were: i) Verticillilum lecanii @ 5gm/L of water; ii) Derisom (Karinjin) @ 2ml/L of water; iii) Margosom (Azadirachtin) @ 5ml/L of water; iv) Lemon grass oil @ 2ml/L of water; v) Dimethoate (Rogor) @2ml/L of water; and vi) Untreated control. Each plot consisted of 2 m x 2.7 m (5.4 m2) with 360 plants (spacing RR 30 cm x PP 5 cm). Field experiment showed that the highest reduction of Lipaphis erysimi (Kalt.) was achieved in Dimethoate (Rogor 30 EC) followed by Derisom but these two treatments were statistically at par during almost all the spray times. Thus, Derisom (botanical) might be the best option in eco-friendly management of Lipaphis erysimi (Kalt.). Int J Appl Sci Biotechnol, Vol 3(3): 537-540